Customer Switching Behaviour - An Evaluation of Factors Affecting Mobile Users - Mallikarjuna, V.; Mohan, G. Krishna (Indian Journal of Marketing, 2010)
Indian mobile services' market has grown manifold in the last five years and the subscriber base had crossed 320 millions by the end of October 2008. The growing affluent-middle-class, low cost of handsets and call tariffs has helped this stupendous growth. Even now, the penetration rate of mobile phones in India, in comparison to other markets like China, Japan and European countries, is low. This presents an enormous opportunity for the Indian mobile service operators to enhance their market share through mindshare. The recent policy initiative of allowing new operators in a circle has added fuel to the competition in the cellular market bringing the call tariffs to the lowest in the world. The fierce competition among the cellular service providers resulted in numerous tariff plans, group plans, contracts (life long validity etc.), and top-up plans. Today, an Indian mobile customer is overwhelmed with the competing offers and service packages from the competing operators.